Effects of dietary yellow mealworm Tenebrio molitor meal and selenium on the growth performance, digestive and absorptive enzyme activity, immune response, skin color, and muscle quality of large yellow croaker Larimichthys crocea - Peng Qu; Zhiyu Zhang; Yang Wu; Shuangjie Tian; Jing Yuan; Zhenhua Wu; Peng Chen; Dong Huang; Mingzhu Pan; Kangsen Mai; Wenbing Zhang (Aquaculture Reports)
The present study aimed to investigate the effects of increasing levels of yellow mealworm Tenebrio molitor (TM) meal as a replacement of dietary fishmeal (FM) and different levels of dietary selenium supplementation on the growth performance, digestive and absorptive enzyme activity, immune response, skin color and muscle quality of large yellow croaker Larimichthys crocea (initial body weight: 189.97 ± 1.01 g). Using a 3 × 2 factorial design, six isonitrogenous (about 47 % of crude protein) and isolipidic (about 10 % of crude lipid) diets were formulated with 3 replacement levels of FM by TM (15 %, 30 % and 45 %) and two supplemented levels of selenium (0.67 mg/kg and 3.78 mg/kg) in the form of sodium selenite. After an 80-day feeding trial, the results showed that 30 % of replacement of dietary FM by TM did not significantly influence the growth performance and feed utilization of large yellow croaker. The supplement level of 1.7 mg/kg Se significantly improved the weight gain and ventral and caudal skin yellow value (P < 0.05). This selenium level led to a decrease in serum triglyceride, malondialdehyde, and 8-hydroxydeoxyguanosine, while increased the activities of intestinal chymotrypsin, γ-glutamyltransferase, acid phosphatase and lysozyme (P < 0.05). The replacement of FM with TM at 15 % and 30 % levels significantly increased the expression of nuclear factor erythroid 2-related factor 2 (P < 0.05). The 1.7 mg/kg dietary selenium reduced the expression of nuclear factor-κb and kelch-like ech-associated protein 1 in both intestine and liver. In conclusion, up to 30 % replacement of dietary FM by TM showed no significant adverse effects on growth and feed utilization of large yellow croaker. Supplementation of 1.7 mg/kg dietary selenium significantly enhanced the growth, feed utilization, anti-oxidative ability, and muscle quality of large yellow croaker. However, there were no interactions between dietary FM replacement level and Se supplement level regarding growth performance, immune response, and muscle quality of large yellow croaker. The Se could mitigate the negative growth effects of over-high dietary TM on large yellow croaker.